2014
DOI: 10.1371/journal.pone.0096524
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage in Buccal Mucosa Cells of Pre-School Children Exposed to High Levels of Urban Air Pollutants

Abstract: Air pollution has been recognized as a human carcinogen. Children living in urban areas are a high-risk group, because genetic damage occurring early in life is considered able to increase the risk of carcinogenesis in adulthood. This study aimed to investigate micronuclei (MN) frequency, as a biomarker of DNA damage, in exfoliated buccal cells of pre-school children living in a town with high levels of air pollution. A sample of healthy 3-6-year-old children living in Brescia, Northern Italy, was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 46 publications
4
39
1
Order By: Relevance
“…When frequencies of nuclear anomalies of condensed chromatin and karyorrhectic and pyknotic cells were compared in different healthy children populations, large variabilities were observed. While some of them (40,50), including our study, had much higher values, others (51) had lower values than the levels obtained in the study by Thomas et al (52). The causes of this variability may, in part, reflect genetic and non-specific exposure differences, or in part, technical factors and differences in the sample preparation and interpretation of the scoring criteria between laboratories.…”
Section: Resultscontrasting
confidence: 53%
“…When frequencies of nuclear anomalies of condensed chromatin and karyorrhectic and pyknotic cells were compared in different healthy children populations, large variabilities were observed. While some of them (40,50), including our study, had much higher values, others (51) had lower values than the levels obtained in the study by Thomas et al (52). The causes of this variability may, in part, reflect genetic and non-specific exposure differences, or in part, technical factors and differences in the sample preparation and interpretation of the scoring criteria between laboratories.…”
Section: Resultscontrasting
confidence: 53%
“…For this purpose, a suspension of scraped BM cells from each sample was prepared [25]. The test tubes containing the cellular suspension were kept at −20°C and sent on ice to the University of Perugia which saw to their staining, fixing on slides and microscopic analysis.…”
Section: Mn Cytome Assaymentioning
confidence: 99%
“…In recent years, studies of MN frequency in the BM cells of children and young adults have shown cytogenetic damage in participants living in areas with high concentrations of particulate matter (PM) or oxidant pollutants [20][21][22][23][24][25]. Recently, Ceretti et al [25] found a higher frequency of MN in the exfoliated buccal cells (EBCs) of pre-school children living in a highly polluted town in the Po Valley in Italy than was observed in a pooled general population of the same age.…”
Section: Introductionmentioning
confidence: 99%
“…Th ough not specifi c for air pollution exposure, biomarkers with the potential for future clinical application include exhaled nitric oxide, micronuclei frequency in buccal mucosa cells, microRNA in induced sputum samples, malondialdehyde in exhaled breath condensate, and serum IL-6 levels. 37,[55][56][57][58] Of the ILDs, IPF, in particular, is age-related, raising the possibility that lifetime cumulative environmental exposures may relate to the advanced cellular senescence seen in this disease. 23,59 Comprehensively characterizing the environmental contributors to fi brogenesis (either directly or through gene and environment interactions) may be an essential step in understanding the complex pathobiology of IPF.…”
Section: Integrating Environmental Exposures Into Disease Models: Th mentioning
confidence: 99%